Efficacy of nanoencapsulated Moringa oleifera L. seeds and Ocimum tenuiflorum L. leaves extracts incorporated in functional soft cheese on streptozotocin-induced diabetic rats - Tarek Nour Soliman; Alshymaa A.Kh. Karam-Allah; Eman M. Abo-Zaid; Dina Mostafa Mohammed (Elsevier, 2024)
Background: In recent years, there has been significant interest in using various plant-based phytochemicals with exceptional biological activities as nutraceuticals to prevent the development and advancement of diabetes mellitus and its severe consequences. The extracts of Moringa oleifera L. seeds and Ocimum tenuiflorum L. leaves are used in herbal therapy due to their beneficial effects in combating various disorders, notably diabetes mellitus Purpose: The paper aimed to investigate the incorporation of both free Moringa oleifera L. seed extract and Ocimum tenuiflorum L. leaves extract and nanoencapsulated using whey protein isolate cold gelation ultra-filtration cheese as natural plant-based functional foods and explore both free and nano-encapsulated ultra-filtration cheese impacts as a novel application on diabetic rats through nutritional parameters, biochemical parameters, physicochemical parameters, and sensory evaluation. Methods: Thirty-six male Sprague-Dawley rats were given only one dose of streptozotocin (35 mg/kg body weight) intraperitoneally. The nutritional and biochemical parameters were assessed. The Moringa oleifera L. seed extract and Ocimum tenuiflorum L. leaves extract were successfully encapsulated, and the best ratio added was 75 mg of both, which gave the best results regarding particle size distribution, surface charge and encapsulation efficiency. Results: The Moringa oleifera L. seed extract and Ocimum tenuiflorum L. leaves extract gave the best results regarding particle size distribution, surface charge, and encapsulation efficiency. Their nano-encapsulated forms had increased the total solids, protein, and ash of ultra-filtration cheese. Moringa oleifera L. seed extract and Ocimum tenuiflorum L. leaves extract, nano-encapsulated in ultra-filtration cheese, gave antioxidant activity stability and significantly captured free radicals. The ultra-filtration cheese samples' sensory qualities evaluations received high marks and were suitable for incorporating Moringa oleifera L. seed extract and Ocimum tenuiflorum L. leaves extract nanoparticles in food systems. Conclusion: The nutritional and biochemical parameters confirmed that both nanoencapsulation forms of natural plant sources and functional soft cheese containing nano-encapsulated Moringa oleifera L. seed extract and Ocimum tenuiflorum L. leaves extract demonstrated a potential anti-hyperglycemic effect without any problems.